Three takes on telecom's troubles. - Guerin, R. (IEEE spectrum)
Spectrum asked three IEEE members from the telecommunications sector to comment on the industry's current woes and prospects. Roch Guerin discusses bandwidth as a commodity and how to deal with it. The impact of technological change on telecommunications is enormous and calls for a shift in business models. Technology is making bandwidth a commodity and it should not matter who supplies it. Competition is vital and commodity providers must be decoupled from value providers. Frank Ferrante points out that the Year 2000 crisis resulted in manufacturers being deluged with orders for new upgraded systems. Vast sums were spent to meet the demand in time. However, when Y2K was over, production stayed high and inventories continued to build, while demand effectively stopped overnight. Dazzling new innovations are needed to compel the masses to spend and manufacturers must apply their resources to deliver quickly and efficiently. Jules A. Bellisio discusses the role of engineers in bringing new ideas to the market place. Many engineers have put together ventures for the sole purpose of attracting capital. The underlying technology and business propositions were there solely to lure the unsuspecting. By allowing engineers to use technology simply to cover for a scam, then the profession is also to blame for the current problems.